The original scores of traditional Chinese medicine constitutions are risk and diagnostic factors in middle‐aged and older adults with sarcopenia - Xin Nie; Chi Wang; He Zhang; Qianhui Liu; Lisha Hou; Yiping Deng; Wenbin Ye; Jirong Yue; Yong He (Aging Medicine, 2024)
Abstract Objective Sarcopenia is a geriatric syndrome that occurs with age and is characterized by a gradual decline in muscle mass, power, and functionality. It serves as a prominent contributor to frailty, disability, and mortality among older individuals. Currently, no standardized global guidelines exist for the diagnosis of sarcopenia. This study aimed to establish the correlation between sarcopenia and the constitutions of traditional Chinese medicine (TCM), considering the connection between physical functioning and sarcopenia. Methods A total of 1441 participants in this study were diagnosed with sarcopenia. The Asian Working Group for Sarcopenia (AWGS) proposed a sarcopenia definition algorithm. To determine the constitution of each participant, classification and determination standards were used in traditional Chinese medicine. This study evaluated the demographics, lifestyles, and self‐reported medical history of individuals diagnosed with sarcopenia through a self‐administered questionnaire. The constitution of the participants was determined using TCM classification and determination standards. Subsequently, we analyzed the results of univariate analysis and multivariate regression and constructed a receiver operating characteristic (ROC) curve. Results Participants who were diagnosed with sarcopenia had substantially lower original Neutral constitution scores (P < 0.050). In comparison to those without sarcopenia, individuals with sarcopenia exhibited notably elevated original Qi‐deficiency, Yang‐deficiency, Yin‐deficiency, Blood‐stagnation, and Qi‐stagnation scores in contrast to those in the healthy group (P < 0.050). The identified risk factors associated with sarcopenia included the following: Neutral (OR = 0.903), Qi‐deficiency (in males, OR = 1.126), Yang‐deficiency (OR = 1.062), Phlegm‐dampness (in males, OR = 0.833), and Blood‐stagnation (in females, OR = 1.089). The highest area under the curve (AUC) was observed for the original neutral constitution score, followed by the Yang‐deficiency and blood‐stagnation scores (0.644, 0.613, and 0.611, respectively). Additionally, the AUC for the combined original scores of all nine constitutions among males reached 0.778. Conclusions In this cross‐sectional study of older people with higher original Qi‐deficiency, Yin deficiency, Yang‐deficiency, Blood‐stagnation, and Qi‐stagnation were associated with sarcopenia. Notably, various TCM constitutions are significantly linked to sarcopenia. There was a significant occurrence of various body constitution types among individuals diagnosed with sarcopenia. The mixture of the nine original constitution scores exhibited good diagnostic performance for sarcopenia in males.